Formação de agenda e processo decisório nos governos FHC e Lula: uma análise sobre a dinâmica e as oportunidades de negociação no processo de tomada de decisão do setor elétrico - França, Cassio Luiz de (2007)
The main objective of this thesis is to analyze agenda setting and the selection of alternatives in two decision making processes in Brazilian federal government public policies. The singularities of decision making processes occur by limiting the range of potential topics that might be of major interest for the executive in a first moment and, subsequently, by selecting the feasible alternatives to be implemented by the public agents. The thesis explores why only certain topics are part of the government agenda and reviews the level of influence of stakeholders on the selection of alternatives processes, where some of them are taken seriously and others are simply neglected. In order to asses the singularities of decision making processes, two case studies were carried out on decision making in the electric sector. The first case study is the discussion of electric power generation in the period previous to the crisis of 2001. The second case study is the creation of a new model for the sector during 2003 and 2004. The central finding of this dissertation is that the core aspects of policy frameworks did not change as long as the dominant coalition that established them remained in the power – despite the change of some secondary aspect that might occur during this period.